Cultivating Wellbeing: Young People and Food Gardens on Tanna, Vanuatu - Mitchell, Jean; Niras, Joan; Niefeu, Lesbeth (Engaged Scholar Journal, 2020)
Gardens in Vanuatu, an archipelago in the SW Pacific, materialize the multiple relationships between land, humans, and the more-than-human world that facilitate self-reliance, and wellbeing. This paper analyzes a collaborative project (2016-18) undertaken on the Island of Tanna in Vanuatu. A project for and with youth and their communities, it aimed to train young people to do basic research on customary food gardens and to document Indigenous customary knowledge, practices, and customary stories about food and gardens. The project started after a catastrophic cyclone destroyed gardens and infrastructure, rendering the self-sufficient islanders dependent on food aid at a time of rising rates of non-communicable diseases (NCDs). There is also concern about the declining interest in traditional knowledge among youth. With about 60% of the population under 30 years of age, this paper argues that youth are critical actors in ensuring the continuity of customary knowledge and practices that are essential for food sovereignty, the maintenance of social relations and wellbeing, all of which are embedded in relational ecologies of care.